2014
DOI: 10.1007/s12032-014-0276-1
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-minutes infusion rate is safe enough for bevacizumab; no need for initial prolong infusion

Abstract: Bevacizumab (Bev) is a vascular endothelial growth factor-A monoclonal antibody that targets tumor angiogenesis. The transfusion rate of Bev is 90 min in the first dose, 60 min in the second and than from the third dose it is 30 min if no hypersensitivity reaction occurs in the first two doses. The purpose of this study determines whether these initial prolonged infusions are really necessary or not. Between 2007 and 2009, we were using the standard schedule for Bev infusions. In July 2009, we reviewed our med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…A summary of retrospective studies of various therapeutic antibodies (bevacizumab, rituximab, daratumumab, and infliximab), as well as prospective studies (ramucirumab and nivolumab) that implemented shortened infusion times and included IRR incidence as an end point was presented (Table S2). [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] Reportedly, a shorter infusion time did not appear to increase the incidence of IRRs in these studies. Thus, the evidence developed using MIDD approaches indicated that the commonly held perception that infusion rate is related to IRR incidence may not hold true for the antibodies studied.…”
Section: Results and Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of retrospective studies of various therapeutic antibodies (bevacizumab, rituximab, daratumumab, and infliximab), as well as prospective studies (ramucirumab and nivolumab) that implemented shortened infusion times and included IRR incidence as an end point was presented (Table S2). [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] Reportedly, a shorter infusion time did not appear to increase the incidence of IRRs in these studies. Thus, the evidence developed using MIDD approaches indicated that the commonly held perception that infusion rate is related to IRR incidence may not hold true for the antibodies studied.…”
Section: Results and Impactmentioning
confidence: 99%
“…Lilly then conducted a literature review for supportive evidence, as suggested by the FDA. A summary of retrospective studies of various therapeutic antibodies (bevacizumab, rituximab, daratumumab, and infliximab), as well as prospective studies (ramucirumab and nivolumab) that implemented shortened infusion times and included IRR incidence as an end point was presented ( Table ) 52–66 . Reportedly, a shorter infusion time did not appear to increase the incidence of IRRs in these studies.…”
Section: Rationale and Implementation Of Midd To Inform The Developme...mentioning
confidence: 99%
“…31 The feasibility of rapid bevacizumab infusion in 30 minutes at the first time has been confirmed, thereby resulting in a significant reduction in chemotherapy chair time and nursing workload. 32,33…”
Section: Bevacizumabmentioning
confidence: 99%
“…The optimal infusion rate may bring economic benefits (e.g., higher patient satisfaction, improved institutional efficiency and more nursing time available for other activities). [29][30][31][32][33][34][35][36][37][38] Endostar Continuous infusion may be a more economical choice compared with traditional intravenous drip administration. 39…”
Section: Economic Efficiencymentioning
confidence: 99%
“…Sehn et al also examined that a 90-minute rituximab administration for more than 1,200 cases and reported that no grade 3 or 4 infusion reactions were observed [8]. As for bevacizumab, trastuzumab, and panitumumab, similar studies have been performed and indicated that it is possible to shorten infusion time [9][10][11][12]. Therefore, we hypothesized that it is possible to shorten the infusion duration of ramucirumab for patients without IRR during the first administration.…”
Section: Salar Et Al Reported Rapid Administration Of Rituximabmentioning
confidence: 99%